Implementasi Layanan Pemeliharaan Kesehatan dan Perawatan pada Anak Usia Dini - Widya Karyatin; Rachman Hasibuan (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Early childhood is experiencing a period of very rapid growth and development. Children's health and nutrition greatly affect the growth and development process. Therefore, health care and nutrition are very much needed to optimize children's development. In general, maintaining children's health which aims to prevent children from contracting a disease, which can interfere with children's learning and intelligence, can be done through: a) maintaining children's personal hygiene and their environment, b) timely immunization, c) maintaining the types of food consumed by children. Children's health care is also adjusted to the child's development. The intensity of health services provided to infants is certainly higher than that of children. This is because at the age of infants, they cannot be independent and still need full assistance from adults. While at the age of children, they must be accustomed and trained to be independent in maintaining personal health with light activities (with parental supervision). As educators, they are required to be able to provide behavioral stimuli and knowledge about how to maintain health in children. Efforts to maintain children's health begin with implementing clean and healthy living habits in everyday life